Improved Safety, Bioavailability and Pharmacokinetics of Zidovudine through Lactoferrin Nanoparticles during Oral Administration in Rats - Kumar, Prashant; Lakshmi, Yeruva Samrajya; C., Bhaskar; Golla, Kishore; Kondapi, Anand K. (PLOS ONE, 2015)
Zidovudine (AZT) is one of the most referred antiretroviral drug. In spite of its higher bioavailability (50–75%) the most important reason of its cessation are bone marrow suppression, anemia, neutropenia and various organs related toxicities. This study aims at the improvement of oral delivery of AZT through its encapsulation in lactoferrin nanoparticles (AZT-lactonano). The nanoparticles (NPs) are of 50–60 nm in size and exhibit 67% encapsulation of the AZT. They are stable in simulated gastric and intestinal fluids. Anti-HIV-1 activity of AZT remains unaltered in nanoformulation in acute infection. The bioavailability and tissue distribution of AZT is higher in blood followed by liver and kidney. AZT-lactonano causes the improvement of pharmacokinetic profile as compared to soluble AZT; a more than 4 fold increase in AUC and AUMC in male and female rats. The serum Cmax for AZT-lactonano was increased by 30%. Similarly there was nearly 2-fold increase in Tmax and t1/2. Our in vitro study confirms that, the endosomal pH is ideal for drug release from NPs and shows constant release from up to 96h. Bone marrow micronucleus assay show that nanoformulation exhibits approximately 2fold lower toxicity than soluble form. Histopathological and biochemical analysis further confirms that less or no significant organ toxicities when nanoparticles were used. AZT-lactonano has shown its higher efficacy, low organs related toxicities, improved pharmacokinetics parameter while keeping the antiviral activity intact. Thus, the nanoformulation are safe for the target specific drug delivery.